Comparison of plasmid profiles, phage types, and antimicrobial resistance patterns of Salmonella enteritidis isolates in the United States. - Rodrigue, D C (1992)
To evaluate the laboratory techniques for subtyping isolates of Salmonella enteritidis, we compared the plasmid profiles (PP), phage types (PT), and antimicrobial susceptibility patterns (AS) of two nationally representative samples of sporadic human S. enteritidis isolates from 1979 (n = 28) and 1984 (n = 37), 43 isolates from 20 outbreaks of S. enteritidis infections between 1983 and 1987, and 46 animal isolates selected from the U.S. Department of Agriculture Veterinary Services Laboratory in 1986 and 1987. Sporadic and outbreak isolates from humans showed similar rates of resistance to at least one of a panel of antimicrobial drugs (23 and 14%, respectively), PT (91 and 98%, respectively), and PP (97 and 100%, respectively). Sixteen different PP were identified in sporadic, outbreak, and animal isolates; two PP accounted for 76% of sporadic and outbreak isolates. Sporadic human isolates were of PT 8 (42%), of PT 13a (37%), nontypeable (9%), of PT 14b (8%), of PT 9a (3%), and of PT 13 (2%). Outbreak human isolates had similar distributions of PT. PT 8 was associated with poultry: 58% (7 of 12) of the poultry isolates but only 24% (8 of 34) of the isolates from other animals were of PT 8 (P less than 0.04). Although antimicrobial susceptibility patterns do not appear as useful as an epidemiologic marker, PP and PT effectively subtyped S. enteritidis.